Mastering project management : - Lewis, James P. (McGraw-Hill, 2008)
For nearly a decade, Mastering Project Management, has been the field's gold standard reference. Now, James Lewis has updated his classic guide, offering both practical, real-world guidance and a focus on higher-level tools and applications that you won't find anywhere else. This fully revised second edition shows project managers and team leaders from all industries how to ramp up and fine-tune managing skills and bring all projects to a successful completion. Carefully avoiding any overlap from his other popular project management titles, Lewis clearly defines your role as a project manager and outlines the steps to mastering project management.